Perlindungan Hukum Hak Prajurit dalam Sengketa Tata Usaha Militer Ditinjau dari Undang-Undang Nomor 31 Tahun 1997 tentang Peradilan Militer dan Kekosongan Pranata Hukumnya (SETARA : Jurnal Ilmu Hukum, 2023)
This article examines legal protection for soldiers in military administrative disputes during a period when the procedural law of the Military Administrative Court has not yet been implemented in detail. The issue is important because legal disputes affecting soldiers' rights continue to arise even though the institutional design promised by Law Number 31 of 1997 on Military Courts remains incomplete. Using normative juridical research supported by doctrinal analysis, the article reviews the concepts of legal protection, legal certainty, and administrative remedies within the military legal system. The study finds that the absence of implementing procedural rules creates a legal vacuum that prevents litigation before the Military High Court from functioning effectively. In practice, soldiers who are harmed by military administrative decisions still rely on administrative objections and restorative or non-litigation mechanisms within the chain of command. The article argues that this interim avenue provides limited protection, but comprehensive legal certainty requires the immediate enactment of procedural regulations for military administrative adjudication.